Food value chain analysis: A review of selected studies for Pakistan and guidelines for further research - ul Haq, Zahoor (International Food Policy Research Institute, 2012)
The study of value chains comprises of two key concepts: value and chain. The term value is synonym to “value added” in the Value Chain Analysis (VCA) as it characterizes the incremental value of a resultant product produced from processing of a product. For agricultural products, value addition can also take place through differentiation of a product based on food safety and food functionality. Price of the resultant product shows its incremental value. The term chain refers to a supply chain indicating the process and the actors involved in the life cycle (from conception to disposal) of a product (Hawkes and Ruel, 2011). Hence, Kaplinsky and Morris (2001, pg. 4) defines VCA as study of the “full range of activities which are required to bring a product or service from conception, through the different phases of production (involving a combination of physical transformation and the input of various producer services), delivery to final consumers, and final disposal after use”. Sanogo (2010) in addition to the movement of a product from one stage to another and identification of the actors, firms and their services, also adds analysis of the institutional support to production at various stages to VCA.